Addition of tumour infiltration depth and extranodal extension improves the prognostic value of the pathological TNM classification for early‐stage oral squamous cell carcinoma. Issue 3 (29th July 2019) - Boeve, Koos; Melchers, Lieuwe J; Schuuring, Ed; Roodenburg, Jan L; Halmos, Gyorgy B; van Dijk, Boukje A; van der Vegt, Bert; Witjes, Max J
Abstract : Aims: In the 8th edition of the American Joint Committee on Cancer TNM staging manual, tumour infiltration depth and extranodal extension are added to the pathological classification for oral squamous cell carcinoma. The currently available 8th TNM validation studies lack patients with conservative neck treatment, and changes in the classification especially affect patients with small tumours. The aim of this study was to determine the potential impact of the changes in the 8th edition pTNM classification on the prognosis and treatment strategy for oral squamous cell carcinoma in a well‐defined series of pT1–T2 patients with long‐term follow‐up. Methods and results: Two hundred and eleven first primary pT1–T2 oral squamous cell carcinoma patients, with surgical resection as primary treatment, were analysed retrospectively. One hundred and seventy‐three patients underwent a neck dissection, and 38 patients had frequent clinical neck assessments. Long‐term follow‐up (median 64 months) and reassessed tumour infiltration depth were available. Classification according to the 8th edition criteria resulted in 36% total upstaging with the T classification and 16% total upstaging with the N classification. T3‐restaged patients ( n = 30, 14%) had lower 5‐year disease‐specific survival rates than T2‐staged patients (81% versus 67%, P = 0.042). Postoperative (chemo)radiotherapy could have been considered in another seven (3%) patients on the basis of the 8th edition criteria. Conclusions: Addition of tumour infiltration depth and extranodal extension in the 8th TNM classification leads to the identification of oral squamous cell carcinoma patients with a worse prognosis who might benefit from an improved postoperative treatment strategy.